2001
DOI: 10.1051/vetres:2001108
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of the UL21 gene in Pseudorabies virus results in the formation of DNA-deprived capsids: an electron microscopy study

Abstract: -We studied the morphogenesis of three pseudorabies virus mutants lacking parts of the gene homologous to the UL21 gene of the herpes simplex virus type 1. The mutants were examined in an SK-6 cell-line, in an SK-6 cell-line expressing the UL21 gene product, in porcine lung alveolar macrophages (PLAM) and in porcine nasal mucosa explants. Although on SK-6 cells and PLAM, the virus-assembly and egress of mutant virus M155, lacking almost the entire UL21 gene, was similar to that of the rescued PRV mutant, M155 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
19
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 24 publications
2
19
0
Order By: Relevance
“…Mutagenesis of the gene in PRV leads to impaired cleavage of the concatemeric viral genome into single-unit lengths (13). Furthermore, the complete absence of U L 21 protein in PRV results in an increase in the number of empty capsids (38). As genome cleavage and encapsidation are linked processes in alphaherpesviruses, inefficient DNA processing may lead to a delay in nucleocapsid assembly, which in turn may lead to delayed transneuronal transmission of infectious particles.…”
Section: Discussionmentioning
confidence: 99%
“…Mutagenesis of the gene in PRV leads to impaired cleavage of the concatemeric viral genome into single-unit lengths (13). Furthermore, the complete absence of U L 21 protein in PRV results in an increase in the number of empty capsids (38). As genome cleavage and encapsidation are linked processes in alphaherpesviruses, inefficient DNA processing may lead to a delay in nucleocapsid assembly, which in turn may lead to delayed transneuronal transmission of infectious particles.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, the PrV UL21 protein had been described as a capsid protein involved in DNA cleavage and packaging (15). In the absence of UL21, formation of DNAdeprived capsids was observed in a cell type-dependent manner (57). In contrast, a UL21 mutant virus we isolated earlier exhibited only a slight effect on replication in cell culture but was strongly attenuated in the natural host (26).…”
Section: Vol 79 2005mentioning
confidence: 92%
“…Electron microscopy showed that UL21-negative virions produced on porcine SK-6 cells or lung alveolar macrophages contained little or no DNA. In contrast, on nasal mucosa explants this defect was not observed, which could indicate that UL21 is involved in packaging of newly replicated DNA in a cell type-specific manner (57).…”
mentioning
confidence: 86%
See 1 more Smart Citation
“…The pUL21 protein of the alphaherpesvirus pseudorabies virus (PrV) has been described as a capsid-associated protein involved in capsid maturation during cleavage and encapsidation of the viral genome (3,33). However, a UL21 mutant of PrV is only slightly impaired in replication in cell culture (13,14) and in a murine intranasal infection model (12) but is strongly attenuated in PrV's natural host, the pig (13).…”
mentioning
confidence: 99%